Aplikasi Mobile Untuk Pengelolaan Dan Promosi Seni Lokal Dengan Sistem E-Commerce Terintegrasi - Bennvenito, Fillan Ivan Luccas; Tashid, T; herwin, H; Zoromi, Fransiskus (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Local art is one of the cultural assets that holds high economic value if managed and promoted effectively. However, many local artists face challenges in marketing their work widely due to limited access and the lack of supportive digital platforms. This study aims to design and develop a mobile web application that facilitates the management and promotion of local art by integrating e-commerce features as a solution to these issues. The application enables artists to digitally market their works, such as weaving, batik, handicrafts, carvings, and paintings, while also making it easier for buyers to access local art products. The integrated e-commerce system includes features such as product catalogs, digital payment, stock management, and transaction tracking. Testing results show that the application improves the efficiency of managing local artworks and significantly expands promotional reach. With this application, it is expected that local artists can become more independent in promoting their work and increasing the economic value of local art. This research also contributes to the development of culture-based technology as part of efforts to preserve local art in the digital era.